Avaliação do desenvolvimento experiencial: emprego da focalização em psicoterapia breve - Marilia Souza da Silveira (2012)
This paper includes two studies. The first one reports initial evidence no to the validity and reliability of the Experiencing Ability Test. One hundred eighteen people resident in Minas Geras, between seven and 87 years and with basic (32.90%), medium (19.00%) and high (48.10%) educationa Ieve|,were part of the study. From them, 55.10% are femaleand 11.90% practice meditation or are expert in psychotherapy. The factor exploratory analysis performed in Mplus 5.2 showed a factor solution with loadings above .89. The Cronbach's alpha was .90, indicating good internal consistency annong the items The cross- judges scores correlation varied between, 69 and .89, indicating reliable scores. Theresults implications are discussed among the clinical psyclnology and the measurement of experiential skills. The second study of this dissertation investigates the effects of abrief psychotherapy within the technique of focusing to change the experiential skill Ievels in patients in situation of ocular prosthesis. The design of case-control study included an experimental group which experienced sessions of focusing. Theexperimental group and control group were eva uated in pretest and postest design , through THE. The effect size of 0,38 indicated that brief psychothenapy with focusing technique, in four sessions, has a snnal-moderate effect in generate changes to the expeiential ability of the patients, although the results do not show statistically significant (p <= 0.05) due to the sample size of the groups